L’entre-deux de Vassilis Alexakis - Alves, Ana M. (2024)
This reflection allows us to examine the impossible place in which the Franco-Greek writer Vassilis Alexakis finds himself. Drawing on Dominique Maingueneau's concept of spatial paratopy, we propose to analyze the paradoxical situation of belonging and non-belonging that deeply characterizes Alexakis' poetics of displacement. This spatial instability, which fuels his creativity, configures the writer's paratopic situation as his constantly travels between Greece and France, Athens, the Cyclades, and Paris. Through his narratives such as Paris-Athènes or Le Cœur de Marguerite, we will attempt to unveil the author's dual insular and cosmopolitan identity. In this constant spatial back-and-forth between Paris, Athens, Tinos, a northern island in the Greek Cyclades, Andros, and the archipelago of Santorini, which evokes his childhood, we will seek to understand these movements marked by a shared existence.